ANTICHOLINERGIC PREMEDICATION FOR PREVENTION OF OCULOCARDIAC REFLEX DURING SQUINT SURGERY - Gilani, Syed Mushtaq; Jamil, Muhammad; Akbar, Farhat; Jehangir, Roomana (Journal of Ayub Medical College Abbottabad, 2005)
Background: Profound bradycardia during eye surgery is potentially serious event. In clinical practice this Oculocardiac Reflex (OCR) is most often encountered during squint surgery. The objective of this study was to assess the occurrence of OCR and prove the effect of anticholinergic premedication (atropine) to prevent OCR. Methods: This study comprises of sixty patients (age 2- 30 years) operated for squint surgery under general anaesthesia. Cases were divided into two groups of thirty each. Group 1 was premedicated with intravenous injection of atropine and Group 2 did not receive any premedication. Patients were monitored during operation for any bradycardia or dysrhythmias. Results: The observed data showed occurrence of 70% OCR in Group 2 as compared to only 10% in Group 1. Severe bradycardia in 40% cases of Group 2 needed intervention by IV injection of atropine. Conclusion: Our study showed that atropine premedication in the patients of squint surgery under general anaesthesia definitely obtunds OCR and prevents any untoward effects of dysrhythmias during eye surgery. Keywords: Oculocardiac Relex (OCR), squint surgery, atropine premedication